A meta-analysis of the Frisch extensive margin elasticity - Ali Elminejad; Tomas Havranek; Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2020)
A key parameter in structural models is the Frisch elasticity of labor supply at the extensive margin, but empirical estimates vary greatly. We provide a quantitative synthesis of the literature. To this end, we collect 723 estimates from 36 studies along with 22 explanatory variables reflecting studies' characteristics and address model uncertainty by Bayesian and frequentist model averaging. Using linear and non-linear techniques, we find that publication bias exaggerates the mean of reported elasticities in the literature from 0.25 to 0.49. Our findings also suggest that two principal characteristics affect the magnitude of estimated elasticities systematically. First, identification bias: studies that follow a quasi-experimental approach tend to report smaller estimates. Second, aggregation bias: studies using macro data tend to report larger estimates. Furthermore, estimates associated with prime age or male workers tend to be systematically smaller, while studies relying on specific-industry data, near retirement workers, and probit regression tend to be larger.
Keywords: E24; J20; J21; C83; 330; Frisch elasticity; extensive margin; meta-analysis; publication bias; Bayesian model averaging